Montessori approach, math education and gender differences: how can teachers manage pupils' math anxiety? - Alice Tovazzi; Barbara Caprara (Pensa MultiMedia, 2019)
Currently, research concerning anxiety and gender gap in mathematics has not yet provided an exhaustive illustration of the phenomenon, observed mostly through the neuropsychological lens. Since in the last twenty years studies in math education (and STEM in general) have shown how arithmetic skills are essential for being active citizens in the technological and digital society in which we live, finding an effective educational answer is fundamental for the future. The aim of the present study is to analyse the characteristics of the educational action of a Montessori teacher, crossing them with evidence obtained from psychology and neuroscience regarding the effects of math anxiety on learning.